(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The stability of mixed tablet dosage forms of Sumatriptan and Naproxen was determined using a RP-HPLC method that was painstakingly created and verified. The ability of this analytical method to reliably quantify both APIs, even in the presence of degradation products, lends credence to its use in stability testing and meets regulatory standards. Acetonitrile and phosphate buffer in a 60:40 v/v ratio made up the optimised mobile phase, which had a flow rate of 1.0 mL/min. The pH was adjusted to 3.0 using orthophosphoric acid. These investigations validated the method’s stability-indicating properties by showing that it can successfully separate analytes from degradation products. Finally, the suggested RP-HPLC technique is ideal for regular quality control, content uniformity testing, and stability investigations of pharmaceutical formulations including Naproxen and Sumatriptan since it is easy to use, quick, precise, and repeatable. It can be used in research and industrial quality assurance settings because it is resilient and meets regulatory validation criteria.